Development of the SCAR marker for genetic purity testing of cotton hybrid - P.Y. SHINDE,; MALAVIKA DADLANI, (Seed Research, 2026)
One of the most important attribute of seed quality i.e. genetic purity was evaluated with the study of genetic purity testing of one intra-hirsutum hybrid (Nathbaba). The electrophoresis profiles of tris soluble proteins, globulins and methanol precipitated fractions failed to differentiate the parents from the hybrid in the Nathbaba hybrid and hence not useful for genetic purity testing. The RAPD analysis was found useful in differentiating the two parents, as well as the female parents from the hybrid. Primer OPA- 07 was selected for genetic purity testing of Nathbaba hybrid. The sequence tagged sites (STMS) markers were unable to differentiate the female parents from the hybrid. The development of SCAR marker from the RAPD polymorphic primer was successfully accomplished in the present study and this approach is suggested to ensure higher reproducibility in testing the genetic purity in cotton hybrid.